That Woman : The Making of a Texas Feminist - Hightower, Nikki Van, 1939- (Book collections on Project MUSE., 2020)
"When Nikki R. Van Hightower stepped into the position of Women's Advocate for the City of Houston in 1976, she quickly discovered that she had very little real power. And when the all-male city council cut her salary to $1 a year after she spoke at a women's rights rally, she gained full appreciation for just what she was up against. Nonetheless, before the job was abolished altogether two years later, Van Hightower went on to help orchestrate the enormously successful US National Women's Conference in Houston, to help found the Houston Area Women's Center and establish its rape crisis and shelter programs, and to host a radio show where she publicly discussed issues of gender, race, and human rights. This eye-opening memoir offers a window into the world of Texas history and politics in the 1970s, where sexual harassment was not considered discrimination, where women's shelters did not exist, where no women were elected to city government, where women in the parks department were prohibited from working outdoors, and where women paid to use airport toilets while men did not. That world that may seem distant and slightly unreal today, so all the more reason to read Van Hightower's journey as a feminist. Her story will remind us that while much has been achieved in gender relations and women's rights, there is much that remains to be done"--